The impact of digital media on mastering grammar for effective TOEFL preparation and performance - Jasrial, Dedi; Zaim, Muhammad; Thahar, Harris Efendi (Journal of Language and Pragmatics Studies, 2025)
In the digital era, numerous studies have highlighted the effectiveness of digital educational platforms in teaching English grammar. However, limited research explores the integration of YouTube videos and the Quizizz platform for enhancing grammar mastery in TOEFL preparation. Addressing this gap, the present study examines the impact of these two digital tools on students’ grammar proficiency and their perceptions of the intervention. This study employs a one-group pre-test-post-test experimental design, involving 42 students from the Registration Certificate for Nutrition program at the Bengkulu Health Polytechnic of the Ministry of Health. Data were collected through grammar tests administered before and after the intervention, along with a student perception questionnaire. The Wilcoxon non-parametric test, using SPSS version 16, and descriptive statistical analysis were applied to evaluate the findings. The results demonstrate a significant improvement in students’ grammar mastery for TOEFL preparation following the use of YouTube and Quizizz. Furthermore, students overwhelmingly perceive these digital tools as highly effective in enhancing their grammar skills. They report increased understanding, motivation, confidence, engagement, and retention of grammar concepts through interactive and multimedia-based learning. These findings underscore the efficacy of digital media in language learning and highlight the benefits of incorporating YouTube and Quizizz into TOEFL preparation courses. Educators are encouraged to integrate such multimedia resources into their teaching strategies to optimize learning outcomes. By leveraging interactive and visually engaging digital platforms, instructors can foster a more dynamic and effective grammar learning experience, aligning with modern pedagogical approaches in English language education.